Reproductive aspects and knowledge of family planning among women with Acquired Immunodeficiency Syndrome - Ivana Cristina Vieira de Lima; Maria da Conceição dos Santos Oliveira Cunha; Gilmara Holanda da Cunha; Marli Teresinha Gimeniz Galvão
ABSTRACT OBJECTIVE To analyze the reproductive aspects and knowledge of family planning among women with Acquired Immunodeficiency Syndrome (AIDS). METHOD Cross-sectional and descriptive study carried out from January to December, 2015, in the outpatient care of infectious disease unit in a hospital located in Fortaleza, Ceará. Data were collected through a form applied by interview in a private setting. RESULTS 102 women participated in the study. Most were aware that they were serologically positive with human immunodeficiency virus (HIV) during prenatal care (96.1%) and did not intend to have more children (63.7%). Women who were less than 39 years of age, had a higher educational level, and a shorter time of antiretroviral therapy had better chances of having children (p≤0.05). Having a steady partner increased the chance of desiring to have children, while tubal ligation was higher among women that did not receive counseling on family planning. Knowledge of family planning was limited because of lack of assistance provided by health professionals.